Social Media for the Dissemination of Educational Videos About Inflammatory Bowel Diseases. (5th August 2022) - van Deen, Welmoed K.; Simpson, Mike; Dupuy, Taylor P.; Khalil, Carine; Bonthala, Nirupama N.; Spiegel, Brennan M.R.
Abstract : INTRODUCTION: To broadly disseminate 5 user-centered educational videos for patients with inflammatory bowel disease and their family and friends on social media. METHODS: Relevant social media users were iteratively identified based on their online behavior. For each video, 2 different accompanying texts were tested. RESULTS: We reached 4.2 million social media users of whom 320, 302 watched at least 50% of the video. A short description resulted in higher view rates than posing an open-ended question. DISCUSSION: We showed the feasibility of large-scale dissemination of health-related educational videos through social media. Our findings can inform future online dissemination approaches of educational content.